Media Health Literacy on Preventive Health Behavior Among Indonesian Women - Arya Wood; Mohd. Nor Shahizan Ali (UIR Press, 2022)
The understanding of media health literacy has been increasing for several decades, along with the basic concept of health literacy among women of the reproductive age group in Indonesia. Media health literacy has been advancing and becoming a strong concept based on the use of technology and the level of education in modern society. The perspective of media health literacy among women in Indonesia is distinguished by the depth of one’s educational background, which then influences their health decisions regarding preventive behaviors. Media health literacy has been significantly connected to health behavior. In contrast, this type of interaction creates a new meaning of media within the context of health literacy, which embodies the new definition of media health literacy. Meanwhile, health behaviors are dependent on the health literacy level, which is connected by the media, with a significant influence on public opinion and clinical procedure. As a result, it has a limitless ability to either reinforce or inhibit preventive health behaviors. As many as 12 Indonesian women with various educational backgrounds were involved in this study, which showed that perspective and preventive health behavior on cervical cancer are associated with media health literacy. The study also suggested the media health literacy pyramid, which stated that respondents’ educational background plays a vital role in influencing preventive health behaviors to make informed health decisions.